Investigation on impact properties of basalt and glass fiber reinforced polyester composites filled with nano silica - Muslim, Mohamad Asrofi (Malaysian NANO-An International Journal, 2023)
The relevance of granite waste is growing alongside the global demand for granite. This waste comprises various forms, including large granite pieces, tiny fragments, dust, and other debris. This research aimed to create a novel composite by incorporating nano silica from granite powder as a filler, combining it with basalt and glass fibres as the matrix, and using polyester as the resin. The fabrication involved Fiber Reinforced Composite (FRP) production through hand lay-up and vacuum silicon moulding to eliminate trapped air during lamination. After fabrication, tests were conducted for hardness, density, and Low-Velocity Impact under dropping weight. The results indicated that introducing nano silica as a filler in polyester resin positively impacted Basalt Fiber Reinforced Polyester Composite (BFRPC) and Glass Fiber Reinforced Polyester Composite (GFRPC). Analysis showed that as the nano-silica content increased, so did energy absorbed, impact strength and ductility index, up to a 1wt% nano-silica concentration. Beyond this point, agglomeration occurred, causing a decrease in these values. The 1 Nano silica Basalt Fiber Reinforced Polyester Composite (1NSBFRPC) material exhibited the highest energy absorption at 103.21J, indicating strong impact strength at 21.27kJ/m2. Conversely, the 1NSGFRPC material demonstrated the highest ductility index at 4.13. In comparison, Carbon Tech Global’s (CTG) energy absorption, initially 25.56J, experienced a significant increase of 303.79%, reaching 103.21J. The impact strength also showed a notable shift, escalating by 396.96% from 4.28 KJ/m2 to an impressive 21.27kJ/m2. This shift in impact strength represented a remarkable 128.2% surge, highlighting the significant influence of integrating nano-silica. This new composite suits truck body carriers and offers environmental benefits. Furthermore, utilising nano silica in this context not only aids in waste reduction within the granite sector but also contributes to sustainable resources.